2016
DOI: 10.1038/srep23389
|View full text |Cite
|
Sign up to set email alerts
|

Improved dialytic removal of protein-bound uraemic toxins with use of albumin binding competitors: an in vitro human whole blood study

Abstract: Protein-bound uraemic toxins (PBUTs) cause various deleterious effects in end-stage kidney disease patients, because their removal by conventional haemodialysis (HD) is severely limited by their low free fraction in plasma. Here we provide an experimental validation of the concept that the HD dialytic removal of PBUTs can be significantly increased by extracorporeal infusion of PBUT binding competitors. The binding properties of indoxyl sulfate (IS), indole-3-acetic acid (IAA) and hippuric acid (HIPA) and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(95 citation statements)
references
References 57 publications
5
90
0
Order By: Relevance
“…This interference resulted from the combination of competitive displacement and allosteric displacement. With both direct competition for the same binding site and binding-induced allosteric alterations in the protein, we could have unexpected increases in the free concentrations of some PBUTs, just as the finding of the study by Tao et al [17], showing that the use of furosemide and ibuprofen simultaneously and significantly improved the removal of IS and 3-IAA by a 2.9 and a 2.1-fold ratio, respectively, in an in vitro HD model.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…This interference resulted from the combination of competitive displacement and allosteric displacement. With both direct competition for the same binding site and binding-induced allosteric alterations in the protein, we could have unexpected increases in the free concentrations of some PBUTs, just as the finding of the study by Tao et al [17], showing that the use of furosemide and ibuprofen simultaneously and significantly improved the removal of IS and 3-IAA by a 2.9 and a 2.1-fold ratio, respectively, in an in vitro HD model.…”
Section: Discussionsupporting
confidence: 47%
“…For example, Böhringer et al [15] modified HDF with the perfusion of hypertonic NaCl solution to increase the ionic strength (HDF-IPIS) and showed that some PBUTs were removed more efficiently under high ionic strength; however, only the free fraction of IS was significantly increased by this technique in a pilot study including HD patients, in which the mass of PBUTs accumulating in spent dialysate was not significantly different between HD and HDF-IPIS [16]. Tao et al [17] reported that a concentration of 1 mM of ibuprofen could increase the free fraction of IS and PCS by a threefold ratio in uremic plasma.…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy is still not completely explained, but differences may due to different intestinal generation or due to different metabolism of toxic compounds in these patients. Another recent study to improve dialytic removal of PBUTs has been proposed using albumin competitors IS, indole-3-acetic acid, and hippuric acid [43] . This in vitro study demonstrated that the infusion of albumin binding competitors such as ibuprofen, furosemide, and tryptophan into the plasma circuit was able to improve the removed fraction of IS from 6.4 to 18.3, of indole-3-acetic acid from 16.8 to 34.5, while for hippuric acid the observed effect was modest.…”
Section: Possible Therapeutic Interventionsmentioning
confidence: 99%
“…As an unbound solute diffuses through the membrane, another molecule will dissociate from plasma albumin to maintain the binding equilibrium, replenishing the low free solute concentration and allowing for its continuous diffusion. A recent study using human whole blood in an ex vivo dialysis model showed that infusing albumin-binding competitors upstream of the dialyzer significantly increases the dialytic removal of PBUTs, further demonstrating that binding and displacement occur very rapidly (36). First, it is conceivable to speculate that solute binding to albumin is rapidly reversible and that the time required for the solute to dissociate from the binding site is shorter in comparison to the transit time of blood through the artificial kidney.…”
Section: Discussionmentioning
confidence: 99%